2008
DOI: 10.1111/j.1469-8749.2008.03017.x
|View full text |Cite
|
Sign up to set email alerts
|

Head shape measurement standards and cranial orthoses in the treatment of infants with deformational plagiocephaly

Abstract: This review aims to determine how head shape is measured and describes the use of orthoses in the management of deformational plagiocephaly. A systematic review was conducted and papers published in English up to and including 2006 were sourced from nine databases. After initial screening, 20 papers were included; three literature reviews and 17 original papers. Of the original papers, eight concerned the method of head shape measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 30 publications
(111 reference statements)
1
55
0
1
Order By: Relevance
“…However, the occurrence of deformational plagiocephaly and/or brachycephaly (DPB) has increased to as high as 48 % of infants [5-12, 11, 13-15]. DPB is diagnosed at birth or shortly thereafter in children with an abnormal head shape caused by extrinsic forces on an infant's malleable cranium [16,17]. DPB presents with varying degrees of unilateral or bilateral occipital flattening and often ventral displacement of the ear, forehead, and cheek on the affected side [11,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the occurrence of deformational plagiocephaly and/or brachycephaly (DPB) has increased to as high as 48 % of infants [5-12, 11, 13-15]. DPB is diagnosed at birth or shortly thereafter in children with an abnormal head shape caused by extrinsic forces on an infant's malleable cranium [16,17]. DPB presents with varying degrees of unilateral or bilateral occipital flattening and often ventral displacement of the ear, forehead, and cheek on the affected side [11,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature describes many variations of helmet therapy (Bialocerkowski et al, 2008, McGarry et al, 2008, adverse outcomes of this treatment modality have been only reported as an observation by a few authors (Clarren, 1981, Loveday andde Chalain, 2001). To date there have been no studies focussed on the adverse effects of helmet therapy (McGarry et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tests for inter-and intra-observer variability require repeated measurements by the trained examiners (Farkas, 1996;Mortenson and Steinbok, 2006) and should follow a standardized measurement program (Farkas, 1994). However, such a standardized program has not yet been adopted for infants (McGarry et al, 2008). Exact anthropometric measurements are challenging, especially in early infancy when children may be uncooperative (Farkas, 1996;Mortenson and Steinbok, 2006).…”
Section: Introductionmentioning
confidence: 99%